Joint Audit and its Impact on The Quality of External Audit: Evidence from Iraq - Rahma, Nahla Ghalib Abdul (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research aims to identify the concept, importance, and objectives of Joint Audit (JA) and the impact of JA on Audit Quality (AQ).Theoretical framework: This researcher relied on the basic concepts of agency theory and the problems emerging from it, as the JA came to reduce these problems in a way that contributes to achieving AQ.Methodology: This researcher relied on the questionnaire form to collect information, using the statistical program SPSS to analyze the questionnaire forms. The study included the JA variable as an independent variable. In contrast, the dependent variable included AQ in terms of the dimension of the auditor's independence, the auditor's performance, and the quality of his report.Results: This research reached a set of conclusions, the most important of which is that the JA impacts the auditor's performance and the quality of the audit reports that the auditors.Research, Practical & Social implications: JA positively impacts the degree of reliability of financial statements.Value/originality: This study adds knowledge and contributes to the limited literature on JA and AQ, especially in Iraq. The study underscores critical insights from the audit market in emerging countries.